2018
DOI: 10.1002/hed.25442
|View full text |Cite
|
Sign up to set email alerts
|

HLA class II expression on tumor cells and low numbers of tumor‐associated macrophages predict clinical outcome in oropharyngeal cancer

Abstract: Background Human papillomavirus (HPV)‐positive oropharyngeal squamous cell carcinoma (OPSCC) is a highly immunogenic tumor and differences in tumor microenvironment might contribute to the improved survival of HPV‐positive OPSCC patient. Methods A comprehensive multivariate analysis with clinical and immune variables (human leukocyte antigen [HLA] I/II, programmed death ligand 1 (PD‐L1), programmed death receptor 1 (PD1), T cells, and macrophages) was performed in 142 O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 55 publications
(92 reference statements)
1
29
0
Order By: Relevance
“…Moreover, and different from the other studies, we found a clear correlation with prolonged survival in patients with high intratumoral levels of these CD14 -CD33 -CD163 + cells. 13 38 39 It has been previously shown by several groups that CD163 + inflammatory, cytokine-producing CD1c + cDC2 cells (DC3) can be found circulating in the blood. 14 15 40 41 We are the first to show that these cells can also be found in the TME of HPV16 + patients with OPSCC, as the CD14 -CD33 -CD163 + cells we found comprise CD14 -CD68 + CD163 + M2 macrophages and CD14 -CD68 -CD163 + CD1c + cDC2.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, and different from the other studies, we found a clear correlation with prolonged survival in patients with high intratumoral levels of these CD14 -CD33 -CD163 + cells. 13 38 39 It has been previously shown by several groups that CD163 + inflammatory, cytokine-producing CD1c + cDC2 cells (DC3) can be found circulating in the blood. 14 15 40 41 We are the first to show that these cells can also be found in the TME of HPV16 + patients with OPSCC, as the CD14 -CD33 -CD163 + cells we found comprise CD14 -CD68 + CD163 + M2 macrophages and CD14 -CD68 -CD163 + CD1c + cDC2.…”
Section: Discussionmentioning
confidence: 99%
“…15–25% of primary HNSCC lesions and 40% of metastatic specimen had a total loss of HLA class I expression. There was no difference in the frequency of HLA class I abnormalities between HPV - and HPV + tumors [ 48 ]. Interestingly, the loss or downregulation of HLA class I and β 2 -m expression was correlated with the loss of chromosomal regions at 6p21.3 and a loss of heterozygosity (LOH) at 6p21.3 and 15q [ 51 , 53 ].…”
Section: The Role Of Classical and Non-classical Hla Class I Antimentioning
confidence: 99%
“…HLA-E expression was recently also found to be expressed on HNSCC [ 63 ]. Regarding PD-L1 expression, its frequency highly varied in the HNSCC tumors depending on the intra-tumoral localization and the tumor specification as PD-L1 expression was higher in the invasive tumor margin than in the tumor center and higher in HPV + than in HPV - HNSCC [ 48 ]. As for HLA-G, PD-L1 expression was more frequent in metastases than in primary tumors [ 64 ].…”
Section: The Role Of Classical and Non-classical Hla Class I Antimentioning
confidence: 99%
“…The expression of classical HLA class I antigens was shown to be diminished at a high frequency varying from 20 up to 80% of HNSCC lesions and cell lines whereas β2-m expression was absent in approximately 16 % of tumors [30] [31] [32] [33]. There was no difference in the frequency of HLA class I abnormalities between HPVand HPV + tumors [34]. Interestingly, the loss or downregulation of HLA class I and β2-m expression was correlated with the loss of chromosomal regions at 6p21.3 and loss of heterozygosity (LOH) at 6p21.3 and 15q [32,35].…”
Section: The Role Of Classical and Non-classical Hla Class I And Antimentioning
confidence: 99%